Establecimiento y formación de uva de mesa (Vitis vinifera L.) "Red globe" y "Thompson seedless" Bajo la influencia de dos pisos altitudinales en la provincia de Loja. - Espinoza Córdova, Paulo Cesar (2019)
The cultivation of table grapes (Vitis vinifera L.), is one of the most widespread in the world. World production for the year 2019 is expected to be 22.1 million tons (USDA, 2019). Currently the data on the formation and growth of the table grape plant is limited, this information is crucial in order to have an optimal structure that ensures an adequate agricultural work. Therefore, there is a need to evaluate its development during the formation process. The main purpose of this investigation was to determine the period of time that the table grape varieties (Vitis vinifera L.) “Red Globe and Thompson Seedless” need in order to reach their basic prior entering the production stage in two altitudinal floorings in the province of Loja. This research work was carried out in two locations or treatments T1 Zapotepamba Technical Training Binational Center sited in Paltas and also T2 in Buenavista, a parish located in Chaguarpamba, both found in the province of Loja, under a randomized bifactorial design, with 2 treatments, 2 varieties and 15 repetitions for each variety. The data was gathered weekly where variables related to Absolute Growth Rate and Relative Growth Rate were recorded based on the increase in stem growth, stem diameter, growth and main branch diameter. Morphological variables such as leaf area, thermal accumulation in the branches’ growth, number of knots, length of knots, cross-sectional area of the trunk and percentage of plants formed will be evaluated. As part of the results, the increase of the stem’s size in the variety Globe network showed a statistical difference having a greater increase up to T2, in contrast to the T1 that was lower in var. Thompson did not present statistical differences since the growth was very similar between treatments. In the TCA for var. Red Globe was higher in T2 with a value of 1.4 cm / day -1 in T1 it was 1.23 cm / day -1, for var. Thompson Seedless the highest TCA was presented in T1 with 1.44 cm / day -1 and in T2 1.38 cm / day -1. In the TCA in the main branches’ growth, there is no difference for var. Red Globe in both treatments, however, the value of T2 was higher with 2.44 cm / day -1 and T1 2.42 cm / day -1, in var. Thompson Seedless showed a difference being the highest value in T2 with 2.45 cm / day -1 and for T1 2.17 cm / day -1. In the foliar area, the adjustment for the Red Globe variety was R2 0.7091 and for Thompson Seedless R2 0.9064. Keywords: table grape, plant formation, structure.